DOES MANAGEMENT OF PRODUCTIVE ZAKAT AFFECT ON MUSTAHIQ EMPOWERMENT IN BAZNAS SOUTH SUMATRA? - Adawiyah, Romadona; Akbar, Dinnul Alfian; Africano, Fernando (Universitas Islam Negeri Raden Fatah Palembang, 2020)
This research aims to discover the influence of management of productive zakat on the mustahiq in the BAZNAS South Sumatra province, Indonesia. Data collection method used in this research utilized questionnaire in likert scale. Wherein all of 30 residents (population) are being used as sample (census technique). The F test, t test and the coefficient determinan (R2) showed that management of productive zakat has a positive and significant impact on mustahiq empowerment in (BAZNAS) south sumatra province Keyword: the management of productive zakat, empowerment of mustahiq.